Temporal perspectives, sensation-seeking, and cognitive distortions as predictors of adolescent gambling behavior: a study in Italian high schools - Mancone, Stefania; Zanon, Alessandra; Marotta, Giulio; Celia, Giovanna; Diotaiuti, Pierluigi (Frontiers in Psychiatry, 2025)
BackgroundAdolescent gambling is an emerging concern, with increasing accessibility through digital platforms. Psychological factors such as sensation-seeking, cognitive distortions, and time perspectives may contribute to gambling behavior during this developmental period. Aims. This study investigated the association between temporal perspectives and adolescent gambling, controlling for sensation-seeking and cognitive distortions.MethodsA total of 1,424 adolescents (Mage = 16.2 years, SD = 1.3) completed self-report measures assessing gambling behavior (PGSI), time perspectives (ZTPI), sensation-seeking (SSSA), and gambling-related cognitions (GBQ). Multiple regression and moderation analyses were conducted.ResultsPresent-hedonistic (β = .42, p <.001) and present-fatalistic (β = .17, p <.01) perspectives were significantly associated with both gambling frequency and severity, independent of sensation-seeking and cognitive distortions. Future orientation was inversely associated with gambling severity (β = –.19, p <.001). Moderation analyses indicated that the combination of high sensation-seeking and high present-hedonism amplified gambling risk. The model explained 32% of the variance in gambling severity.ConclusionsTemporal orientation plays a distinct role in adolescent gambling behavior beyond traditional dispositional and cognitive factors. Interventions should incorporate time-awareness strategies, helping adolescents shift toward future-oriented thinking while addressing sensation-seeking tendencies through targeted risk management and engagement in alternative rewarding activities.